Antifungal activity of synthetic xanthenone against fluconazole-resistant Candida auris and its mechanism of action - Ramli, Amirah Hani; Jayathilaka, E.H.T. Thulshan; Dias, Mawalle Kankanamge Hashita Madhawa; Abdul Malek, Emilia; Jain, Neha; An, Jongkeol; Churchill, David G.; Rukayadi, Yaya; Swain, Puspanjali; Kim, Cheol-Hee; de Zoysa, Mahanama; Mohd Faudzi, Siti Munirah (Academic Press, 2024)
Candida auris, an emerging multidrug-resistant fungal pathogen discovered in Japan in 2009, poses a significant global health threat, with infections reported in about 25 countries. The escalation of drug-resistant strains underscores the urgent need for new treatment options. This study aimed to investigate the antifungal potential of 2,3,4,4a-tetrahydro-1H-xanthen-1-one (XA1) against C. auris, as well as its mechanism of action and toxic profile. The antifungal activity of XA1 was first evaluated by determining the minimum inhibitory concentration (MIC), time-kill kinetics and biofilm inhibition. In addition, structural changes, membrane permeability, reactive oxygen species (ROS) production, and in vitro and in vivo toxicity of C. auris after exposure to XA1 were investigated. The results indicated that XA1 exhibited an MIC of 50 μg/mL against C. auris, with time-kill kinetics highlighting its efficacy. Field emission scanning electron microscopy (FE-SEM) showed structural damage in XA1-treated cells, supported by increased membrane permeability leading to cell death. Furthermore, XA1 induced ROS production and significantly inhibited biofilm formation. Importantly, XA1 exhibited low cytotoxicity in human epidermal keratinocytes (HaCaT), with a cell viability of over 90 % at 6.25 μg/mL. In addition, an LD50 of 17.68 μg/mL was determined in zebrafish embryos 24 h post fertilization (hpf), with developmental delay observed at prolonged exposure at 6.25 μg/mL (48–96 hpf). These findings position XA1 as a promising candidate for further research and development of an effective antifungal agent.